2020
DOI: 10.1101/2020.08.12.248294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Posterior Insular Cortex is Necessary for the Consolidation of Tone Fear Conditioning

Abstract: The insular cortex (IC) is notably implicated in emotional and cognitive processing; however, little is known regarding to what extent its two main subregions play functionally distinct roles on memory consolidation of conditioned fear tasks. Here we verified the effects of temporary functional inactivation of the anterior (aIC) and posterior IC (pIC) on contextual and tone fear memory. Rats received post-training bilateral infusions of the GABAA receptor agonist muscimol into either the aIC or pIC and were te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It seems likely to be. The engagement of the aIC in the retrieval of CFC is intensity-dependent, as its post-training functional inhibition impairs recent retrieval after stronger trainings (Alves et al, 2013) but not weaker ones (de Paiva et al, 2021). This dependence on the training intensity was also reported in the PrL in mice (Matos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely to be. The engagement of the aIC in the retrieval of CFC is intensity-dependent, as its post-training functional inhibition impairs recent retrieval after stronger trainings (Alves et al, 2013) but not weaker ones (de Paiva et al, 2021). This dependence on the training intensity was also reported in the PrL in mice (Matos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral experiments were conducted in two identical automated fear conditioning chambers (Med-Associates, Inc., St. Albans, VT) connected to a computer interface enabling video recording, analysis and automated measurement of the rat’s freezing behavior in real time. The chambers and software used were previously described in detail (de Paiva et al, 2021; dos Santos Corrêa et al, 2019). Freezing measure was automated (VideoFreeze Version 1.12.0.0, MedAssociates) and set for less than 20 movement units for at least 30 frames (1s) (Bueno et al, 2017; Moreira-Silva et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…An earlier lesion study in rats has found evidence for a role of the pInsCx in fear learning (Shi and Davis, 1999), while others have not (Brunzell and Kim, 2001; Lanuza et al, 2004). More recent studies using pharmacological inactivation have described roles of the pInsCx in safety learning (Foilb et al, 2016), and in fear memory consolidation (Casanova et al, 2016; de Paiva et al, 2021). Also, the notion of a pInsCx to LA connection has not been confirmed in recent anatomical studies in mice, which found outputs from the pInsCx to the central amygdala (CeA), but only weak ones to the LA (Gehrlach et al, 2019; Gehrlach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%